Evaluation of DFO-HOPO as an octadentate chelator for zirconium-89. Issue 61 (13th July 2017) - Allott, L.; Da Pieve, C.; Meyers, J.; Spinks, T.; Ciobota, D. M.; Kramer-Marek, G.; Smith, G.
Abstract : The future of 89 Zr-based immuno-PET is reliant upon the development of new chelators with improved stability compared to the currently used deferoxamine (DFO). Abstract : The future of 89 Zr-based immuno-PET is reliant upon the development of new chelators with improved stability compared to the currently used deferoxamine (DFO). Herein, we report the evaluation of the octadentate molecule DFO-HOPO (3 ) as a suitable chelator for 89 Zr and a more stable alternative to DFO. The molecule showed good potential for the future development of a DFO-HOPO-based bifunctional chelator (BFC) for the radiolabelling of biomolecules with 89 Zr. This work broadens the selection of available chelators for 89 Zr in search of improved successors to DFO for clinical 89 Zr-immuno-PET.